Hospital Management Functions: A Literature Review - Yusrawati Yusrawati; Muhardi Muhardi (Andalas Obstetrics And Gynecology Journal, 2023)
Hospital management is a process of organizing the available resources to support the efficiency and effectiveness of healthcare services provided. The main functions of hospital management include operational management, cost and financial management, materials management, and human resource management. This literature study aims to review each hospital management function based on previous studies within the last five years (2019-2023) obtained from scientific database searches. The inclusion criteria were studies with topics correlated to the four categories of hospital management functions and written in Indonesian/English. Articles that were published from books were excluded. A total of eight studies which were published in accredited journals and can be accessed in full-text form, were analyzed. The results of this study demonstrate that good management will improve overall hospital performance. High-quality financial management will support optimizing the availability of supporting materials for clinical and diagnostic services in hospitals. In addition, adequate human resources planning and organizing, as well as an appropriate work system design, will acknowledge the need for human resource development to increase the professional competence needed to provide health care in the hospital.